2-year impact of an Older People Short Stay Unit team working across emergency areas in the over-75s. (2019) - Lisk, Radcliffe; Watts, Paula; O'Sullivan, Ruth; Pagkalinawan, Maryln; Reyes, Kristine; Foan, Zoe; Spencer, Charlotte; Rawlings, Francesca; Sills, David; Clancy, Laura; Stevenson, Kelly; Chikusu, Clarence
No abstract available